Historical and contemporary records of the angular rough shark Oxynotus centrina (Chondrichthyes; Oxynotidae) in Turkish waters - KABASAKAL, H. (Mediterranean Marine Science, 2010)
During the last 58 years, only 12 angular rough sharks were recorded in Turkish waters. Rare captures of the species in the area needs an immediate action for the conservation of O. centrina. To protect the habitat of O. centrina, strict regulations should be implemented for diving in the localities, where the angular rough sharks occur regularly. Protecting the habitat of the angular rough shark is an urgent need before subjecting O. centrina to 100% protection in the seas of Turkey.